Colonic growth factors (G-CSF, GM-CSF) and chemokines (MCP-1, MIP-1β) in severe ulcerative colitis - Yevgeny A. Konovich; K. Ye. Shirokikh; M. V. Shapina; Igor L. Khalif (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine the content of growth factors (G-CSF, GM-CSF) and chemokines (MCP-1, MIP-1β) in resected colon specimens of patients with severe ulcerative colitis (UC). Material and methods. Overall 48 biopsy specimens of the colonic mucosa resected at 7 patients with total UC were investigated. All patients underwent colectomy due to severe disease, resistant to conservative treatment. Inflammation activity was determined according to severity of erosive and ulcerative lesions of the colon. Growth factor and chemokine levels in supernatant fluid after centrifugal separation of homogenate of 10 mg biopsy specimen were investigated by the protein analyzer «Bio-Plex» («Bio-Rad», USA). Biopsy specimens of uninvolved colonic mucosa resected in 10 cancer patients were used as a control. Results. Growth factor and chemokine levels were significantly elevated in colonic biopsy specimens of UC patients in comparison to that of controls: G-CSF 52,5±17,0 and 0,4±0,1 pg/10 mg (p MIP-1β - in 17 (89,4%) and 12 (63,1%) of 19 colonic biopsies of UC patients with severe inflammatory activity. Conclusions. Significant increase in neutrophil growth factor level G-CSF and monocyte chemokine MCP-1 was observed in colonic biopsy specimens of UC patients at widespread destructive and inflammatory ulcerative process.